PERKEMBANGAN ISLAM DI KELANTAN: ANALISIS TERHADAP MANUSKRIP SEJARAH NEGERI KELANTAN (The Development of Islam in Kelantan: Analysis on the Manuscript of Sejarah Negeri Kelantan) - Zainal Abidin, Mohd Zahirwan Halim; Hamzah, Norhayati Haji (Journal of Al-Tamaddun, 2018)
This research focuses on the history of the development of Islamic rule in the state of Kelantan from the time of Sultan Mansur Syah (1465-1526 AD) to Long Sulaiman Bin Long Bahar (1733-1756 AD) based on the manuscript of Sejarah Negeri Kelantan (SNK) written by Abdullah Bin Hj. Wansa Patani in 1309 H / 1891 M. This study is a qualitative research that employed the method of content analysis. The technique of documentation and the instrumen of interview were applied in data collection while inductive approach was utilized for data analyzing. The findings show that Islamic rule in the state of Kelantan at that time was dominated by three descendants that of Sultan Mansur Syah, Jembal and Patani. The Islamic government in Kelantan has gone through a long process of historical development involving the kingdom’s throne. In addition, the research reveals that the most remarkable period of reign was that of the Cik Siti Wan Kembang (1024-1088 H / 1615-1677 M) as political crisis did not occur and the people were living peacefully due to the rapid economic development. Besides that, Kelantan had become increasingly popular as a trading center. Furthermore, the development of Islamic rule in Kelantan has also experienced some conflicts and events such as civil war and diplomatic relations with the Siamese state.